FOREWORD - Belcev, Tole (PALIMPSEST / ПАЛИМПСЕСТ, 2018)
The sixth issue of the international scientific journal “Palimpsest” is not only a confirmation of the efforts of the editors of this scientific publication, but also of the management and the academic staff of the Faculty of Philology at Goce Delcev University - Stip for raising the journal’s quality in every sense to a higher level in relation to all previously published issues. In fact, the papers published in this issue and their solid scientific and research value illustrate the growing interest of linguists, literary theorists, historians and critics, cultural scientists and teaching methodologists from Macedonia and abroad for participating in the creation of each upcoming issue. Namely, the sixth issue of “Palimpsest” contains 25 research, theoretical and review papers by authors not only from Macedonia (from Goce Delcev University in Stip, St. Kliment Ohridski University in Bitola, and St. Cyril and Methodius University in Skopje), but also from other countries such as Serbia, Croatia, Slovenia, Bosnia and Herzegovina, Slovakia, Turkey, Ivory Coast and Morocco, in the five permanent sections of the journal: Language, Literature, Culture, Teaching Methodology and Book Reviews.